Class After Industry A Complex Realist Approach - Byrne, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
The transition to twenty-first century post-industrial capitalism from the 'welfare' industrial capitalism of the twentieth century, has affected the ways in which class is lived in terms of relational inequality and the factors that structure identity. Class After Industry takes a complex realist approach to the dynamics of individual lives, places, the social structure and analyses their significance in terms of class. A wide range of quantitative and qualitative studies are drawn on to explore how 'life after industry' shapes class, and the consequent potential for social change. The book will be of interest across the social sciences and beyond, to those concerned with how class forms might translate into political action.
Chapter One: Introduction -- Chapter Two: A Complex Realist Take On Theorizing Class -- Chapter Three: After Industry and After the Welfare State -- Chapter Four: Class and Culture: The Dynamics of Cultural Change -- Chapter Five: How Class is Lived: The Dynamics of Lives and the Dynamic of Society -- Chapter Six: Class in Space -- Chapter Seven - Understanding How Class Is Lived and Acted in Post-Industrial Capitalism -- Chapter Eight: Conclusion: What Can Be Done. .
Keywords: Social structure; Equality; Industrial organization; Social sciences -- Philosophy; Demography; Population; Welfare state; Labor; History; Social Structure; Industrial Organization; Social Theory; Population and Demography; Welfare; Labor History